Tax Digitalization and Cooperative Compliance: A Trust-Mediated Model of Tax Compliance: Study of Corporate Taxpayers Registered with Kanwil DJP Jakarta Timur - Siti Dewani; Hari Setiyawati (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Indonesia’s persistently low tax ratio compared to ASEAN and G20 countries reflects structural challenges in strengthening tax compliance. Although Jakarta contributes the largest share of national tax revenue, performance among regional tax offices remains uneven, with East Jakarta recording the lowest realization in 2021–2022. This study investigates the effect of tax service digitalization and cooperative tax compliance on taxpayer trust and their subsequent impact on tax compliance. Using a quantitative approach, data were collected through questionnaires from 150 corporate taxpayers registered in East Jakarta and analyzed with SmartPLS 4.1. The results reveal that both tax service digitalization and cooperative tax compliance significantly enhance taxpayer trust and compliance. Taxpayer trust also exerts a significant positive effect on compliance and mediates the relationship between the independent variables and tax compliance. This study contributes conceptually by integrating the Theory of Planned Behavior and the Slippery Slope Theory to explain compliance behavior through trust, and contextually by focusing on East Jakarta, the weakest-performing regional office. The findings provide theoretical insights and practical implications for designing tax policies that leverage digitalization and cooperative approaches to foster taxpayer trust and strengthen compliance. Keywords: Tax Digitalization, Cooperative Tax Compliance, Taxpayer Trust, Tax Compliance